Generalized procedure of separation of variables and reduction of nonlinear wave equations - Barannyk, T. A.; Barannyk, A. F.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We propose a generalized procedure of separation of variables for nonlinear wave equations and construct broad classes of exact solutions of these equations that cannot be obtained by the classical Lie method and the method of conditional symmetries.